Ethos Amerika sikap masyarakat terhadap kapitalisme dan demokrasi Herbert McClosky, John Zaller ; diterjemahkan oleh J.F.R. Sardjono ; editor, Alex H. Rambadeta - McCLOSKY, Herbert; Zaller, John; Sarjono, J.F.R; Rambadeta, Alex H (Gadjah Mada University Press, 1988)
xxii, 516 hlm ilus 21 cm